Expectations of pregnant women prior to fetal ultrasound - Bok, Eularnia Janine (My University, 2017)
Background Expectations and knowledge of pregnant women prior to fetal ultrasound are well documented in developed countries. Women have generally been shown to have appropriate and reasonable expectations and knowledge. The main objective of this study was to examine whether the views of women in our setting are similar to findings from studies in developed countries. Methods This was a descriptive study done on pregnant women attending the ultrasound department and antenatal clinic at Rahima Moosa Mother and Child Hospital. An interview questionnaire was administered before the ultrasound scan. Results Two hundred and fifty women were recruited. The most frequently expressed expectation was to determine sex of baby (n=154). This was followed by wanting to know the baby’s wellbeing and health (n=136). All the women interviewed had expectations. The majority of women did not know that fetal anomalies could be detected at fetal ultrasound (n=235), this was statistically significant (p=0.003) and was correlated to educational level. Almost half the women did not know the purpose of the ultrasound for which they were referred for (n=124). Conclusion Most women had appropriate expectations in keeping with studies from developed countries. Lack of education was directly linked to poor knowledge of fetal ultrasound. This study has identified areas where patient education is needed regarding fetal ultrasounds.
Keywords: Pregnant Women; Ultrasonography, Prenatal